Post-Purchase Experience in Online Shopping and Their Impact on Customer Satisfaction at Blibli.Com - Soesanto, Maria Yosephine (ProBisnis : Jurnal Manajemen, 2023)
This study aims to determine the effect of Post-Purchase Experience on Customer Satisfaction and Future Purchase Intention on the use of the Blibli.com application in Surabaya. This research method uses an online survey of 200 respondents in Surabaya who have used the Blibli.com application, especially those who have used the return facility. The collected data were analyzed using the Structural Equation Modeling (SEM) measurement model assisted by using SPSS Version 24.0 and AMOS Version 23.0 applications. The results of this study found that several variables in the Post-Purchase Experience, namely the Shipping Service and Tracking Service variables were not supported on Customer Satisfaction on the use of the Blibli.com application in Surabaya. Other variables, namely Return service and Customer Service have an effect on Customer Satisfaction, and Customer Satisfaction has an effect on Future Purchase Intention.